ANALISIS PERBEDAAN KINERJA UMKM SEBELUM DAN SESUDAH PEMBERIAN KREDIT PROGRAM KEMITRAAN (Studi Pada Mitra Binaan PT Telekomunikasi Indonesia, Tbk Sub Area Malang) - Indrasta, Gilang Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyze the impact of the credit partnership programs on the performance of Micro, Small and Medium Enterprises (MSMEs) partners of PT. Telkom Malang Area. This study analyzes the performance of financial and non- financial SMEs between before and after receiving credit partnership program. The research method of this study is a quantitative study method using paired t-test and ratio analysis. Secondary data are used and collected using the documentation of SMEs financial statements. The results show that the credit partnership programs have no impact on SMEs financial performance, but the credit programs can improve non-financial performances. The results of paired t-test and analysis of the financial performance ratios show that credit partnership programs can improve the turnover of SMEs, but does not have an impact on Net Profit Margin (NPM) and Return on Assets (ROA). Non-financial performances show an increase in growth in the numbers of costumers.Keywords: credit partnership program, turnover, NPM, ROA, customer growth